Global buckling investigation on laterally-unrestrained Q460GJ steel beams under three-point bending. (15th February 2019) - Yang, Bo; Zhang, Yue; Xiong, Gang; Elchalakani, Mohamed; Kang, Shao-Bo
Highlights: Experimental tests were conducted on doubly-symmetric welded Q460GJ steel beams against lateral torsional buckling. Numerical models were developed for steel beams to quantify their lateral torsional buckling resistances. Comparisons were made between numerical results and design curves from different national codes. Abstract: This paper presents an experimental and numerical study on the global buckling behaviour of doubly-symmetric Q460GJ steel beams under three-point bending. A total of eight simply-supported beams with different slendernesses and height-to-width ratios were tested in the experimental programme. To achieve the required loading and boundary conditions, a special loading system was designed for the beams so that the vertical load applied at the mid-span through a hydraulic jack could move with the beams in the lateral direction, and a set of steel rollers was placed in the supports. All eight beams failed in lateral-torsional buckling. Finite element models were also developed for the beams, in which initial geometric imperfections and residual stresses were considered. The model was validated against experimental results, and a reasonably good agreement was obtained. A series of parametric study was carried out to gain a deep understanding of the effects of slenderness and height-to-width ratio on buckling factor. Comparisons were made between numerical data and calculated values in accordance with different national codes.